The state of criminological studies in East Asia - Liu, Jianhong (Southernising criminology, 2024)
A significant development in criminology over the past decades has been the growing recognition of the prevalent Western-centric bias (Carrington, 2017; Liu, 2007a; Moosavi, 2018, 2019). There are well-established calls to decolonize criminology and rectify this bias. Asian criminology has played an essential role in this development (Moosavi, 2018). To respond to the Western-centric bias adequately, accurate knowledge of the situation of criminology in Asia is essential. However, to date, much of the summarization and evaluation of the state of criminology research in Asia has been based on subjective perceptions and evaluations. There has been no systematic collection of all criminological studies about Asia to examine the state of criminology studies in Asia. Asian criminology has grown rapidly, particularly since 2009 when the Asian Criminological Society was established (Belknap, 2016; Moosavi, 2018). This paper comprehensively collects all criminological and criminal justice research articles addressing Asian-related topics published in all influential SSCI English-language criminology journals from 2009 to 2021. The paper asks and answers a series of factual questions about the basic situation of criminology studies in East Asia. The findings about the distributions of these studies provide facts that lay a reliable foundation for accurately pursuing further directions and adequate approaches to decolonization and rectifying Western-centric bias in criminology.